CONNECTIVE AMBITION AND CREATIVE CAUTION AMONG HOMELESS USERS OF FACEBOOK - Marler, Will (AoIR Selected Papers of Internet Research, 2018)
This work-in-progress considers how Chicago’s homeless navigate privacy on social media. I refer to "connective ambition" to describe the co-mingling of personal goals with a perception of the power derived from accumulating ties on social networking sites. Preliminary interviews and participant observation with unstably housed Chicagoans suggests that with great ambition comes great risk for exposure to unwanted advances and digital crooks. These risks may be magnified for those lacking personal computers and sufficient computer literacy. At stake is our understanding of how activity on social media translates into social capital. The paper promises to inject new concern for those who stand to gain the most from social networking online.